How Political Narratives Affect the Self-Enforcing Nature of Interim Constitutions - Prieto, Marcela; Verdugo, Sergio (Springer Nature, 2021)
This essay seeks to contribute to the literature that asks how interim constitutions can become self-enforcing norms capable of producing a successful constitution-making process. It uses the Chilean constitution-making process as an example to theorize on how the political narratives associated with the November 2019 Agreement, which sets the framework for constitutional change, can influence its self-enforcing capacity. The authors identify and reconstruct the two prevailing normative theories underlying the Chilean constitution-making process: the evolutive and the revolutionary narratives. These present themselves in both radical and moderate versions. While evolutive ideas emphasize institutional continuity, consensus-building, and an incrementalist approach to constitutional change, revolutionary arguments rely on the constituent power theory and push for a profound social transformation that can break with the past. Even though these narratives are in tension with each other in many respects, they have both influenced the design of the rules of the constitution-making process. The authors claim that the self-enforcing capacity of the interim constitution partly depends on whether, and to what extent, the moderate versions of these narratives succeed or prevail in the political discourse.
Keywords: 56 Ciencias Jurídicas y Derecho; ODS 16 - Paz, justicia e instituciones sólidas; Interim constitutions; Constitutional enforcement; Constitution-making; Chile